Beyond principlism:towards a reconceptualization of bioethics - Casasola Rivera, Wilmer (2016)
The article brings on board the epistemological problem of reductionism in bioethics, this is, the principlism. It criticizes the lack of conceptual thoroughness of the four principles and the academic negligence of passively accepting them with no further interpretation and considering bioethics a product of these four main principles. This reductionism in bioethics is called the dogma of bioethics. The article discusses that to be able to go beyond principlism it is imperative a reconceptualization of bioethics as a first step.